Effects of Sevoflurane Anesthesia on Cerebral Lipid Metabolism in the Aged Brain of Marmosets and Mice - Mao, Haoli; Zhu, Jiao; Cheng, Yanyong; Shi, Lingling; Chen, Xiao; Zhou, Ren; Xue, Zhenyu; Liu, Siyu; Qiu, Zilong; Jiang, Hong (Frontiers in Molecular Neuroscience, 2022)
Objective: In the lipid-rich brain, lipids performed signalling processes associated with the control system of the cell cycle, stress and inflammatory reactions, as well as maintained brain and cellular homeostasis. The effects of general anesthesia on brain impairment in the elderly were controversial and complex. The study sought to evaluate whether long-term exposure of aged marmosets and mice to sevoflurane was associated with lipidome metabolism in the brain. Methods: Six marmosets over 8-year-old and ten mice aged 18 months were divided into the sevoflurane anesthesia and control groups, respectively. Marmosets in the sevoflurane anesthesia group were exposed to 1.5%-2.5% sevoflurane and 100% O2 for 6 hours. Mice anesthetized with sevoflurane were exposed to 3% sevoflurane and 60% O2 for 6 hours. All prefrontal cortex tissues of marmosets and mice were harvested for the analysis of lipid metabolism. Results: Compared to the control group, we found that phosphatidylethanolamine (PE) (18:0/22:5), PE (16:0/22:5), PE (18:2/22:5), PE (14:0/22:5), and PE (18:1/22:5) increased significantly in the prefrontal cortex of marmosets in the sevoflurane group, while triglyceride (TAG)56:5- fatty acid (FA) 20:4, TAG58:10-FA22:6 and TAG60:10-FA22:6 decreased obviously. For aged mice, we indicated that lipid metabolites phosphatidic acid (PA) (18:1/20:2) and TAG52:5-FA20:4 in the sevoflurane group increased remarkably, but PE (14:0/22:4), diglyceride (DAG) (16:1/18:2), and lysophosphatidylcholine (LPC) (16:1) + AcO decreased markedly. More deeply, sevoflurane anesthesia resulted in the presence of 70 specific lipid molecules in mice and marmosets. The enriched lipid subclasses were mainly monoacylglycerophosphoethanolamines and five other subclasses. Conclusion: Sevoflurane caused slight changes in lipid metabolism in the brain, but it was not sufficient to affect its metabolic pathway. Importantly, the effects of sevoflurane on lipid metabolism in the brain may differ in aged marmosets and mice.